Respostas

A melhor resposta!
2014-06-15T20:17:01-03:00
4-Simplifique as frações:
a) x² - 16 / x -4b)
x² - 4x -5 / x + 1
c)
x -1 / x² - 2x + 1


a)  x² - 16/x - 4

   x² - 16         (x - 4)(x + 4)         (x-4)( x + 4) : (x-4)         x + 4
---------------- = -------------------  =    ----------------------------   =   ----------  = x + 4
   x - 4                x - 4                    x - 4        :(x-4)            1


b) x² - 4x - 5/x + 1

   x² - 4x - 5           (x +1)(x - 5)     (x+1)(x+5)  : (x+1)      x + 5
------------------------ = ----------------- = -----------------------------= ---------- =   x + 5
    x + 1                   x + 1              x + 1       : (x+1)           1



c)   x-1/
 x² - 2x + 1

      x - 1               x - 1                x - 1        : (x -1)          1
------------------ =  -------------------- = -------------------------- =   -------------- = 1/x-1
  x² - 2x + 1        (x-1)(x-1)          (x-1)(x-1)   : (x-1)          x - 1
 
1 5 1